Gut-Brain Connection : The Role Of Gut Microbiome in Preventing Stroke - Baiq Annisa Pratiwi; Putu Diah Ananda Putri Atmaja; Qurrata’yuni Pratiwi; Ilsa Hunaifi (Unram Medical Journal, 2022)
Stroke is the second most prevalent cause of death in the world and placed third in disability causes worldwide. Beside affecting health, the reduced quality of life and the expensive cost of its treatment also has a huge impact on social, physical, and psychological aspect of a patient. Currently, the management of stroke is centered on currative and rehabilitative effort. Hence, the preventive efforts are on demand. Several studies have showed that there is a link between gut microbiota and the nervous system in somehing called the Gut-Brain Axis (GBA). Intestinal microbiota plays an important role in GBA. Therefore, maintaining the balance of intestinal microbiota, through neuronal or non-neuronal two-way communication between both of those system, is a promising way to prevent stroke.